Physical literacy, health and interactive aging: a position paper - Rebecca J. Lloyd; Stephen Smith; Derya Sahingil (Frontiers Media S.A., 2024)
Physical literacy (PL), a concept commonly associated with the early years, physical education, and youth sport development, can become a meaningful determinant of health and longevity for the adult and older adult population. A review of 55 recent publications from 2018 to 2023 that encompassed physical literacy conceptual frameworks, assessments, and intervention-based studies was undertaken through an heuristic inspired by the philosophy which gave birth to PL. With particular interest in how PL has evolved in response to the needs of an aging population, this position paper tracks a key shift in focus from the individual to the relational context. It references positive interaction and social participation in recent models as significant features of an across-the-lifespan PL perspective.The concluding position is that fostering joyful inter-action be at the heart of PL promotion, resource development and assessment practices, especially in the case of an aging population.